Self-efficacy and compliance with treatment regimen in tuberculosis - Naghib, salam; Abed Saeedi, jila; Ezzati, zhaleh; Zayeri, farid (Advances in Nursing & Midwifery, 2013)
Abstract Background and aim Tuberculosis is a major public health problem in the world, affecting 30% of the world’s population. Treatment of tuberculosis is the most effective strategy to stop the spread of the disease. However, non-adherence remains an important cause of treatment failure. It is believed self-efficacy may affect patient’s compliance to treatment regimen. The purpose of this study is to determine the correlation between self-efficiency and treatment compliance in tuberculosis patients attending to medical centers of Kurdistan University of medical sciences Kudistan, Iran. Materials and Method A descriptive-correlational design was used. The sample of the study consisted of 161 tuberculosis patients attending to health centers in Kurdistan province .Data were collected using a self efficacy questionnaire and the review of patients' medical records. he validity of the questionnaires were determined by 12 experts through the content validity and formal validity methods. The minimum index of content validity for self-efficiency questionnaire was calculated to be 75.5 percent and that of compliance was 83.5 percent. The reliability of the questionnaires was determined using the Krunbach's Alpha-Test. The coefficient of reliability for self-efficiency questionnaire and compliance questionnaire were 0.94 and 0.97 respectively. Data were analyzed using the SPSS 16 software. Findings The average age for patients was 58±12 years old. 61.5 percent of studied samples were male and the rest were female. The amount of compliance by patients was moderate (average scores of 30.23) and correlated to age, marital status, job, income level, education and place of living but, its relation to gender was not statistically significant. The amount of self-efficiency of the majority of patients was moderate (41.6 percent) and it was also related to age, marital status, job, income level, education and place of living but its relation to gender was not statistically significant. There was a direct and strong correlation between self-efficiency and compliance (P<0.001, r=0.90). Conclusion The reason why the compliance level in this study has been higher with respect to the previous similar studies could be due to the implementation of direct supervision and control system over treatment. In this study there was a significant correlation between compliance and self-efficiency which was in consistency with most studies in this field while in Hamilton (2000) no significant correlation between the two variables was reported. Given that the correlation coefficient of Pearson in this study is positive and close to 1 (P < 0.001, r = 0.90), it indicates a direct and strong correlation between the two variables of self-efficiency and compliance. Corresponding Author: Zhila Abed Saeedi, Assistant professor Shahid Beheshti Department of Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran Iran . Email: jilasaeedi@sbmu.ac.ir REFERENCES ) -$ %&' ( .) ) ) = ! $ .". 7"! ! 2G , .(1388)9 7"! ! )PG \ - -Allami M (2003). [Tuberculosis control]. Iran Journal of Nursing. 16 (34) 14-19. -Bandura A (1994). Self_Efficacy, Encyclopedia of Human Behavior. 4 th edition. New York, Academic Publishing -Brus H Van de Laar M Erik Taal E et al (1997). Compliance in rheumatoid arthritis and the role of formal patient education. Seminar in Arthritis and Rheumatism. 26 (4) 702-710 -Dawoodi Pour M et al (2007) [Assessment of knowledge and attitudes of tuberculosis patients regarding the disease, and treatment compliance in Kalaleh]. Proceedings of 18th National Congress on Tuberculosis. Ministry of Health and Medical Education. 277. (Persian). -Hamilton M D (2000). The influence of self efficacy on compliance functional ability and quality of life in a cardiac rehabilation population. A Thesis for the Degree of Master of Science in Physical Activity Studies. University of Regina -Nokes K et al (2012). Focus on Increasing Treatment Self-Efficacy to Improve Human -Immunodeficiency Virus treatment adherence. Journal of Nursing Scholarship. 44 (4)403-410 -Pishkar Mofrad Z (2001). [Knowledge and attitudes of tuberculosis patients regarding the disease, and treatment compliance].MS in nursing Thesis. Shahid beheshti Faculty of Nursing and Midwifery. Tehran Iran.(Persian) -Rafeeaie S (2007) [Epidemiology of smear-positive pulmonary tuberculosis in Golestan provience Iran]. Proceedings of 18th National Congress on Tuberculosis. Ministry of Health and Medical Education. (Persian). -Sajadi Sh (2007). Assessing patients’compliance with tuberculosis treatment regimen using urin tests in Tehran. Phamacology Professional Doctoral Thesis. Tehran University of Medical Sciences.Tehran -Sameeaie A et al (2007). [Time from symptom onset to laboratory diagnosis and initiation of treatment of tuberculosis]. Proceedings of 18th National Congress on Tuberculosis. Ministry of Health and Medical Education.176. (Persian) -Scherer Y et al (2001).Knowledge, attitudes and self efficacy and compliance with medical regime number of emergency department visits and hospitalization in adults with asthma.The Journal of Acute and Critical Care.30 (4) 250-257 -Smeltzer S Bare B Hinkle J et al (2004). Brunner and Sudarth’s Text Book of Medical Surgical Nursing. 10th edition Philadelphia Lippincott Williams & Wilkins Publishing. -Surdarth's Text Book of Medical Surgerical Nursing. 10 th edition. Philadelphia Lippincott Williams & Wilkins publishing. -Thomas L Sargent R Michels Pl et al (2001). Identification of the factors associated with compliance to therapeutic diet in older adults with end stage renal diseases. Journal of Renal Nutrition. 11 (2) 80-89 -Stanford patient education center. Chronic disease self efficacy scales [On line] available at: [http://patienteducation.stanford.edu/research/secd32.html] Accessed 12 November 2008